(untitled) (Madhyabindu Journal, 2021)
The present study analyzes the critical discourse analysis of Malala Yousafzai’s speech delivered in the United Nations in July, 2013 from the perspective of social and educational women empowerment and especially it looks at how social power is legitimized by the specific leading entities. It examines the relationship of language, events, practices, socio- cultural structures and relations to understand how the texts are ideologically formed by the relations of power. The analysis was conducted following Fairclough’s three-D model of Critical Discourse Analysis.